Human Immunodeficiency Virus-1 Drug Resistance Patterns Among Adult Patients Failing Second-Line Protease Inhibitor-Containing Regimens in Namibia, 2010–2015. (12th January 2018) - Sawadogo, Souleymane; Shiningavamwe, Andreas; Roscoe, Clay; Baughman, Andrew L; Negussie, Taffa; Mutandi, Gram; Yang, Chunfu; Hamunime, Ndapewa; Agolory, Simon
Abstract: Three hundred sixty-six adult patients in Namibia with second-line virologic failures were evaluated for human immunodeficiency virus drug-resistant (HIVDR) mutations. Less than half (41.5%) harbored ≥1 HIVDR mutations to standardized second-line antiretroviral therapy (ART) regimen. Optimizing adherence, viral load monitoring, and genotyping are critical to prevent emergence of resistance, as well as unnecessary switching to costly third-line ART regimens.